Perspektif Bioetika dan Etika Islam: Penggunaan Metode CRISPR dalam Ketahanan Pangan - Arenalda Nur Rizqita; Chiquita Kamila; Mukhtar Ghulam Halim; Tri Cahyanto; Yuni Kulsum (Tumbuhan : Publikasi Ilmu Sosiologi Pertanian Dan Ilmu Kehutanan, 2024)
With the rapid increase in global population and the ongoing depletion of agricultural land, food security faces an escalating threat. CRISPR genetic engineering technology offers immense potential to enhance crop resilience and productivity. However, its application raises significant ethical concerns, both from a bioethical perspective and within the framework of Islamic values. This article examines core principles of bioethics and Islamic ethics to explore the morally conscious integration of genetic technology. Through a comprehensive literature review, it underscores the necessity of a collaborative approach involving scientists, policymakers, and religious leaders to establish ethical guidelines for its responsible use. The findings highlight the critical need to strike a balance between technological innovation and the preservation of moral principles. By adhering to ethical standards rooted in both modern bioethics and Islamic teachings, genetic technologies such as CRISPR can be harnessed to address food security challenges by improving crop productivity and fortifying resistance to diseases and extreme environmental stressors, without compromising moral integrity.